2014
DOI: 10.1007/978-3-662-43539-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Polymerization with Non-metallocene Catalysts (Early Transition Metals)

Abstract: In this chapter, recent developments of so called non-metallocene early transition metal (group 3-5) complexes as the catalyst precursors for olefin polymerization have been described. These catalysts display unique characterisitics especially for ethylene (co)polymerization, and high isospecificity ([mmmm] [ 99.6 %) in propylene polymerization has been achieved in some catalyses. The ligand modification plays an essential key role not only for the catalytic activity, but also for control of tacticity and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 157 publications
(183 reference statements)
0
9
0
Order By: Relevance
“…Transition-metal alkyl complexes are among the most important reagents or intermediates in organic reactions, and the study of their reaction chemistry has been recognized as an important subject for better understanding especially in catalysis cycles, reaction pathways, and design of efficient catalysts. The metal alkyl species play a key role in olefin polymerization, the core technology for the production of polyolefins in the chemical industry. Since classical Ziegler type vanadium catalyst systems display unique characteristics (highly reactive toward olefins exemplified as production of ultrahigh molecular weight polyethylene with narrow molecular weight distributions), the reaction chemistry of vanadium–alkyl complexes should be considered as an important subject in the field of catalysis , and organometallic chemistry. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition-metal alkyl complexes are among the most important reagents or intermediates in organic reactions, and the study of their reaction chemistry has been recognized as an important subject for better understanding especially in catalysis cycles, reaction pathways, and design of efficient catalysts. The metal alkyl species play a key role in olefin polymerization, the core technology for the production of polyolefins in the chemical industry. Since classical Ziegler type vanadium catalyst systems display unique characteristics (highly reactive toward olefins exemplified as production of ultrahigh molecular weight polyethylene with narrow molecular weight distributions), the reaction chemistry of vanadium–alkyl complexes should be considered as an important subject in the field of catalysis , and organometallic chemistry. …”
Section: Introductionmentioning
confidence: 99%
“…Early transition-metal–alkyl bonds have been known to be more nucleophilic than those with late transition metals, and these are thus highly reactive toward Brönsted/Lewis acids. For example, cationic alkyl complexes, proposed active species for olefin polymerization, are formed by treating the dialkyl analogues with Al alkyls or borate through protonolysis or alkyl abstraction. ,, These metal alkyls are generally rapidly reacted with alcohols (or phenols, ArOH) via protonation or coordination and a subsequent hydrogen transfer pathway (Scheme ). It has been, however, reported that steric crowding in tetrakis­(alkyl)-chromium­(IV) , and zirconium­(IV) complexes [exemplified as Cr t Bu 4 and Zr­(CH 2 t Bu) 4 ] and (arylimido)­vanadium­(V) trialkyl complex (described below) contributes to greater stability toward oxygen and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…; employed as catalysts for production of EPDM (synthetic rubber) etc. ], 24,3445 development of efficient vanadium complex catalysts is considered to be an attractive and important subject. 24,4245 It has been reported that (imido)vanadium(V) complexes containing the anionic ancillary donor ligand (aryloxo, 4649 imidazolidin-2-iminato, 50 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…], 24,3445 development of efficient vanadium complex catalysts is considered to be an attractive and important subject. 24,4245 It has been reported that (imido)vanadium(V) complexes containing the anionic ancillary donor ligand (aryloxo, 4649 imidazolidin-2-iminato, 50 etc.) 24,4250 and the chelate anionic donor ligand, 5158 as shown in Chart 1, exhibit promising catalyst behaviors in the presence of the Al cocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, interest in developing new complexes that can be used as olefin oligo-/polymerization catalysts has once again attracted considerable attention. Several complexes with different metal centers were used to study the effect of ligand substitution on olefin oligomerization and polymerization activity and selectivity. Iron- and cobalt-based catalysts with bis­(imino)­pyridine olefins have high activity and selectivity for ethylene oligomerization and co-polymerization with methylaluminoxane (MAO). Alt and colleagues reported the use of the bis­(imino)­pyridine–vanadium­(III) complex with MAO as a co-catalyst for olefin-selective oligomerization. ,, The structure of the pre-catalyst has no great influence on the activity of the dimer, but it has a great influence on the distribution of the product.…”
Section: Introductionmentioning
confidence: 99%